EVALUASI PENERAPAN PARIWISATA BERWAWASAN LINGKUNGAN DAN BUDAYA BERDASARKAN NILAI-NILAI TRI HITA KARANA DI FIVELEMENTS (PURI AHIMSA), MAMBAL, BADUNG, BALI - Ni Putu Ratna Sari; A.A.G. Raka Dalem (Environmental Research Center (PPLH) of Udayana University, 2012)
A study on evaluation of implementation of concept of environmentally and culturally friendly tourism based on Balinese life phylosophy of the “Tri Hita Karana” (THK) has been undertaken at Fivelements (Puri Ahimsa) hotel, in Mambal, Badung Regency, Bali between September and October, 2011. Data were collected based on on site observation by reserarchers accompanied by conducting interview to management and employees and checking documents. Evaluations were undertaken refering to evaluation checklist measures of the THK Tourism Awards. Results of the evaluations were then classified into excellent, good, moderate, fair/pass and fail (affiliate). Results of the study showed that the implementation of the THK phylosophy at Fivelements were classified into excellent with overall performance score of 93.33. The score acchieved by Fivelements in general was better than those of hotels participants of the THK Awards in Bali in 2009 (86). From the three aspects, achievements of implementation of THK for community aspects (pawongan) at Fivelements was the highest among others, with the performance score of 96.67. This better that performance of cultural aspects ‘parhyangan’ with achievement score of 96.00 and environmental aspects ‘palemahan’ with achievement score of 85.56. Accross the three aspects of THK (culture, community, and environment), achievements for environmental aspects were observed to have most number of points need to be improved, that was on 50 % of its existing checklist measures. Meanwhile for the culture and community aspects, the hotel performance may still able to be improved on 13 % of its measure checklist points. On environmental aspects, the lowest score achieved was 2 out of maximum 5, ie. on checklist L.13 whcih refering to handling of hazardous materials. On culture aspects, the performance of the hotel which got the lowest score of 3 was on checklist point H.2, which was dealing with availability of shrines within the temple. On ‘pawongan’ (community) aspects, the lowest score achieved was 3 on checklist point W.16. W.16 checklist point was dealing with length of stay. Length of stay of guests in the hotel in average was between 4 and 8 days, the parameter of which was expected should be more than 12 days.